Weak decays of triply heavy baryons - Zhen-Xing Zhao; Fu-Wei Zhang; Qi Yang (European Physical Journal C: Particles and Fields)
Abstract In this work, we investigate the weak decays of ground-state triply heavy baryons. We first obtain the form factors using the light-front quark model in the three-quark picture, and then apply them to arrive at some phenomenological predictions, including the decay widths of semileptonic decays and nonleptonic decays. Our results are expected to be helpful for the experimental search for triply heavy baryons.